Implementasi Kebijakan Pengadaan Barang / Jasa Pemerintah di Kabupaten Morowali Utara - Ruben Gusran Willem; Slamet Riadi; Intam Kurnia (Journal of Innovative and Creativity, 2026)
The study purpose was to analyze the implementation of the policy on announcing the General Procurement Plan (RUP) through the Electronic General Procurement Plan Information System (SIRUP) in North Morowali Regency and to identify supporting and inhibiting factors that influence policy effectiveness. The study also aimed to assess the gap between regulatory expectations and actual practices within regional government work units. Materials and methods. This research used a qualitative descriptive approach. Primary data were collected through in-depth interviews with PA, KPA, PPK, RUP operators, and officials at the Procurement of Goods/Services Unit (BPBJ). Secondary data were derived from RUP documents, government regulations (Perpres 16/2018, Perpres 46/2025, and LKPP Regulation No. 11/2021), as well as circular letters issued by the local government. Data were analyzed using the Miles, Huberman, and Saldana model covering data condensation, data display, and conclusion drawing. Data validity was maintained through source triangulation, technical triangulation, and document verification. Results. The findings show that although the implementation of the RUP announcement policy generally aligns with national regulations, its execution in North Morowali Regency has not been fully optimal. Communication from BPBJ was clear yet unevenly distributed. The most dominant obstacle was resource limitations, including unstable internet networks, limited technical competence, multitasking workloads, and frequent operator turnover. Disposition among implementors varied, with some demonstrating strong commitment while others lacked awareness of deadlines. The bureaucratic structure provided SOPs but lacked enforcement mechanisms, particularly local sanctions, resulting in inconsistent compliance. Conclusions. The study concludes that a policy implementation gap exists due to imbalances across four key variables: communication, resources, disposition, and bureaucratic structure. Strengthening operator capacity, improving technological infrastructure, increasing supervision, and establishing local regulatory sanctions are essential steps to ensure more effective and timely implementation of the RUP announcement policy in North Morowali Regency.